Coadaptation between mother and offspring: why not? - Jason B Wolf; Michael Cowley; Andrew Ward (PLoS Biology)
A Formal Comment has challenged the interpretation of a study into an imprinted gene, maintaining that conflict, rather than mother-offspring co-adaptation, provides a better mechanistic explanation. Here authors of the original Research Article reply.